Consenso e conflito na região da Serra do Papagaio - Junqueira, Mariana Gravina Prates (2018)
This thesis studies the socioenvironmental conflicts by focusing on the relationship between society and conservation units of integral protection in the south of Minas Gerais. It is a case study of the Serra do Papagaio State Park, that sought to understand not only the regional and historical context and its influence on the emergence of the conservationist imaginary, but also the creation of the units and their impact over surrounding communities, which carry peculiar sociocultural characteristics. The interdiction of the use of the territory by the communities is problematized in relation to the current model of conservation, analyzing the correlation of man and nature and the ways that diverse ecological imaginaries are created. Thus, different perceptions and social and symbolic constructions from the rural communities, here named traditional hill country communities, are inside the conflict. In order to expand the analysis and establish a contraposition to the Brazilian model, the National Park of Picos de Europa, in Spain, is also analyzed. In this Park, even though inhabitants are allowed to use the territory, conflicts still exist. The implemented conservation model, through the creation of conservation unities of integral protection, is inserted as a proposal to solve the environmental crisis of the capitalist industrial urban model. This model, though, has revealed itself as both unable to accomplish its objectives and also responsible for aggravating environmental injustice, social exclusion and conflicts. Thus, in order to implement a democratic and participatory management, a paradigmatic and societal change is necessary, allowing another management of the territory and natural resources, one that is equitable, fair and inclusive, a post-development proposal